To work or not to work: The economics of a mother's dilemma - Julie L. Hotchkiss; M. Melinda Pitts; Mary Beth Walker (Federal Reserve Bank of Atlanta, 2011)
Utilizing linked vital statistics, administrative employer, and state welfare records, the analysis in this paper investigates the determinants of a woman's intermittent labor force decision at the time of a major life event: the birth of a child. The results indicate that both direct and opportunity labor market costs of exiting the workforce figure significantly into that decision. Further, the analysis reveals the importance of including information about the mother's prebirth job when making inferences about the role various demographics play in the intermittent labor force decision.
Keywords: J22; J13; J17; D01; D91; 330; labor supply behavior; intermittent; labor market exit; labor leisure choice model